The Role of Non-canonical and Canonical Inflammasomes in Inflammaging - Cyr, Brianna; Hadad, Roey; Keane, Robert W.; de Rivero Vaccari, Juan Pablo (Frontiers in Molecular Neuroscience, 2022)
Neurodegenerative diseases currently affect millions of people worldwide and continues to increase in the expanding elderly population. Neurodegenerative diseases usually involve cognitive decline and are among the top causes of death. Thus, there is a critical need for the development of treatments and preventive strategies for neurodegenerative diseases. One of the risk factors of neurodegeneration is inflammaging, a low level of chronic inflammation due to old age. We have previously shown that the inflammasome contributes to inflammaging in the central nervous system (CNS). The inflammasome is a multiprotein complex of the innate immune response consisting of a sensor protein, apoptosis speck-like protein containing a CARD (ASC), and caspase-1. Our lab has developed a humanized monoclonal antibody against ASC (anti-ASC). Here, we analyzed cortical lysates from young (3 months old), aged (18 months old), and aged anti-ASC treated mice for the expression of canonical and non-canonical inflammasome proteins. We show that the protein levels of NLRP1, ASC, caspase-1, and caspase-8 were elevated in the cortex of aged mice, and that anti-ASC decreased the expression of these proteins, consistent with lower levels of the pro-inflammatory cytokine interleukin (IL)-1. Additionally, we show that these proteins form a novel NLRP1-caspase-8 non-canonical inflammasome comprised of NLRP1, caspase-8 and ASC. Moreover, these inflammasome proteins were present in neurons and microglia in young and aged mice. Together, these results indicate that a novel NLRP1-caspase-8 non-canonical inflammasome is present in the cortex of mice and that anti-ASC is a potential therapeutic to decrease inflammasome-mediated inflammaging in the CNS.